The Value of Ampe Madeceng in The Bugis Local Wisdom of Batutanengnge Village and Its Relevance with Islamic Education Values - Baso, Baso; Natsir, Muh; Aini, Nur; Takdir, Andi (International Journal on Advanced Science, Education, and Religion, 2024)
Bugis local wisdom has unique characteristics reflected in the concept of “ampe madeceng” values, which underline the importance of good behavior in Bugis culture. This article aims to investigate the meaning, values ​​and practices of ampe madeceng in the context of Bugis local wisdom, and to identify its relevance to Islamic educational values. This type of research is qualitative with an educational ethnography approach, conducted through in-depth interviews with community leaders, religious leaders and related community members, and participatory observation with Bugis community members in Batutanengnge Hamlet who hold tightly to the values ​​of ampe madeceng in their daily lives. The research findings show that the values ​​of ampe madeceng include: Assitulungeng (helping each other), Asseddingeng (unity/ukhuwah), Sipakaraja (honoring each other), Mappakatuna ale (low self-esteem), Siparennuangi (trusting each other). These values ​​play an important role in maintaining social harmony and promoting cooperation in Bugis society. All the values ​​contained in ampe madeceng are in line with Islamic principles, such as good ethics, solidarity, mutual respect and mutual trust. Therefore, Islamic education can play a role in strengthening and developing these values ​​in Bugis society, creating individuals who are better in moral and ethical aspects.